The justification of diet supplementation of the Polish national team of athletes - Czaja, J.; Lebiedzinska, A.; Szefer, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Nutrition is an important aspect of an athlete`s training program. Every deficiency and excessive intake of nutritive elements may negatively influence sportsman performance especially high class athletes. However, for various reasons, not all athletes are able to consume a diet that meets nutritional needs and thus resort to nutritional supplements with the intention of preventing deficiencies and even enhancing performance (1, 2, 3). The aim of the study was to examine the justification of the diet supplementation. The investigation was carried out on a group of 62 athletes, members of Polish national team of middle and long distance runners (24 women aged between 19-31 and 38 men aged between 18-36). General information concerning respondents, their nutrition (food consumed within 24 hours before an interview) and their diet supplementation (frequency and quality) was gathered using the method of questionnaire interview at training camps and sport competitions. Values of energy and nutritive elements contents in athlete`s diets were calculated by means of a computer program "Wikt 1.3" based on current tables of food products` nutritional value prepared by the National Food and Nutrition Institute in Warsaw (2001). In the result of the investigation concerning diets quality some abnormalities has occurred. The examined daily food portions of women (W) and men (M) supplied amount of energy (2892 kcal-W; 3955 kcal-M) sufficient to fulfill daily requirement in case of moderate active people, not high class athletes. The investigated diets provided too low energy from carbohydrates and proteins limited by greater percentage of delivered energy from fat. The quantity of macroelements (Ca, P, Na, K, Mg), microelements (Zn, Cu, Mn) and vitamins (A, D, B group, C) in the analyzed diets was sufficient to fulfill daily requirement of athletes. The examined diets provided insufficient amount of Fe and vitamin E to ensure against potential deficiency. According to diet supplementation 100% of the examined women and 94,7% of the examined men used dietary supplements. Most of the investigated athletes reached for carbohydrates powder products, vitamin-mineral products, vitamins C and B group, ferrum and magnesium supplements. Moreover, the examined runners also often enriched their diet in BCAA and carnitine. In the analyzed daily food rations of Polish national team of runners only carbohydrates, ferrum and vitamin E supplementation seems to be justified.